RELIGIUSITAS DAN SEKSUALITAS REMAJA PERKOTAAN: STUDI TENTANG PERILAKU PELAJAR KOTA LHOKSEUMAWE, ACEH - Mumtazul Fikri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This study concludes that the religiosity and sexuality of students in the city of Lhokseumawe are good. The conclusion of this study is different from the publication which states that the free sex of students in the city of Lhokseumawe is the first rank in Aceh. This study aims to find information about the religiosity and sexuality of Lhokseumawe city students, the causes of sexual behavior deviations from Lhokseumawe city students, and the Lhokseumawe city government's solution to stem the deviant sexual behavior of students. This research is a case study research, where data collection is done through in-depth interviews, documentation, and observation. The results showed that, firstly, the religiosity of students was classified as good as evidenced by the pattern of Islamic school uniforms, attitudes and verbal behavior were generally good although some still needed guidance. Attitude and verbal behavior are strongly influenced by domicile origin, economic strata, and parental education. Second, student sexuality is also classified as good as evidenced by the absence of evidence of free sex among students, opposite-sex relationships are still within reasonable limits, although they still require guidance. The sexuality of students at school is strongly influenced by the care of parents in the family. Third, the researchers did not find evidence of free sex in Lhokseumawe city students, but deviations in verbal behavior in the form of pornographic remarks were still found. This behavior is strongly influenced by the socio-cultural area of origin, economic strata, and parental education. Fourth, the solution of the Lhokseumawe city government in stemming student sexual behavior deviations is divided into 3 levels. (1) at the regional level, sterilizing areas have the potential for lewdness, such as the mobile reservoir area, KP3, and Krueng Cunda. (2) the gampong level, by optimizing the potential for religiosities, such as religious tactical funds of 2 million per village, and umrah rewards for the teungku. (3) school level, with religious programs, such as congregational dhuhur prayers, regular Friday taushiah, Ramadan Islamic boarding schools, and al-Qur'an reading programs.